Crucial conversations tools for talking when stakes are high ebook - Patterson, Kerry (2011)
The New York Times and Washington Post bestseller that changed the way millions communicate "[ Crucial Conversations ] draws our attention to those defining moments that literally shape our lives, our relationships, and our world. . . . This book deserves to take its place as one of the key thought leadership contributions of our time." —from the Foreword by Stephen R. Covey, author of The 7 Habits of Highly Effective People "The quality of your life comes out of the quality of your dialogues and conversations. Here's how to instantly uplift your crucial conversations." —Mark Victor Hansen, cocreator of the #1 New York Times bestselling series Chicken Soup for the Soul® The first edition of Crucial Conversations exploded onto the scene and revolutionized the way millions of people communicate when stakes are high. This new edition gives you the tools to: Prepare for high-stakes situations Transform anger and hurt feelings into powerful dialogue Make it safe to talk about almost anything Be persuasive, not abrasive